Underlying pharmacological mechanisms of psilocin-induced broadband desynchronization and disconnection of EEG in rats - Tylš, Filip; Vejmola, Čestmír; Koudelka, Vlastimil; Piorecká, Václava; Kadeřábek, Lukáš; Bochin, Marcel; Novák, Tomáš; Kuchař, Martin; Bendová, Zdeňka; Brunovský, Martin; Horáček, Jiří; Pálení ček, Tomáš (Frontiers in Neuroscience, 2023)
Introduction Psilocybin is one of the most extensively studied psychedelic drugs with a broad therapeutic potential. Despite the fact that its psychoactivity is mainly attributed to the agonism at 5-HT2A receptors, it has high binding affinity also to 5-HT2C and 5-HT1A receptors and indirectly modulates the dopaminergic system. Psilocybin and its active metabolite psilocin, as well as other serotonergic psychedelics, induce broadband desynchronization and disconnection in EEG in humans as well as in animals. The contribution of serotonergic and dopaminergic mechanisms underlying these changes is not clear. The present study thus aims to elucidate the pharmacological mechanisms underlying psilocin-induced broadband desynchronization and disconnection in an animal model. Methods Selective antagonists of serotonin receptors (5-HT1A WAY100635, 5-HT2A MDL100907, 5-HT2C SB242084) and antipsychotics haloperidol, a D2 antagonist, and clozapine, a mixed D2 and 5-HT receptor antagonist, were used in order to clarify the underlying pharmacology. Results Psilocin-induced broadband decrease in the mean absolute EEG power was normalized by all antagonists and antipsychotics used within the frequency range 1–25 Hz; however, decreases in 25–40 Hz were influenced only by clozapine. Psilocin-induced decrease in global functional connectivity and, specifically, fronto-temporal disconnection were reversed by the 5-HT2A antagonist while other drugs had no effect. Discussion These findings suggest the involvement of all three serotonergic receptors studied as well as the role of dopaminergic mechanisms in power spectra/current density with only the 5-HT2A receptor being effective in both studied metrics. This opens an important discussion on the role of other than 5-HT2A-dependent mechanisms underlying the neurobiology of psychedelics.